Unemployment rate and its relationship with government size, trade, inflation, urbanization, and economic growth in Romania - Ali Moridian; Magdalena Radulescu; Muhammad Usman; Seyed Mohammadreza Mahdavian; Alina Hagiu; Luminita Serbanescu (Heliyon)
Unemployment is an important phenomenon affecting all economies, especially during crises such as the recent COVID-19 pandemic. Besides, the government size is significant for all the formerly planned and centralized economies, like the Central and Eastern European countries. This study aims to investigate the impact of government size, income tax, economic growth, inflation, trade openness, and urbanization process on the unemployment level in Romania from 1991 to 2021. After testing the nonlinearity property, the findings of the nonlinear autoregressive distributive lag (NARDL), estimations show a positive influence of urbanization on unemployment. Conversely, government size significantly reduces the unemployment rate in Romania. Inflation and trade are negatively associated with unemployment, while taxation has a positive impact. In this regard, the Romanian authorities should adopt appropriate measures to support governmental expenditure, they need to collect budgetary tax that can reduce the unemployment rate, unless some efficiency measures are adopted such as defeating tax evasion which is high in Romania.